2018
DOI: 10.1016/j.aap.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Driver distraction by smartphone use (WhatsApp) in different age groups

Abstract: This paper investigates the effect that texting with WhatsApp, one of the most common applications for instant messaging, exerts on driving performance. Because distracted driving also affects older drivers, who can have seriously compromised vision, we also analysed the associations between visual-function parameters and driving performance. A total of 75 drivers, experienced in sending WhatsApp messages (≥10WhatsApp messages/week), participated in this study and were divided into four age categories. Visual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 46 publications
(69 reference statements)
4
46
2
Order By: Relevance
“…In this context, our results demonstrate that older drivers drive less efficiently, presenting a higher SDLP and driving longer distances outside their lane, even though they try to correct the vehicle’s position, as evidenced by the higher SD of the steering wheel angular velocity. These results are in general agreement with previous studies, which found that older drivers have a greater incidence of lane excursions [ 34 ], more difficulties changing lane [ 35 ], and less control over the vehicle’s position in unexpected events or divided attention tasks [ 27 ]. The reduced visual capacity observed in older drivers could be responsible for most of these changes, as it affects visual guidance abilities and visual attention span, making older drivers slower and less accurate when detecting all the stimuli on the road [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this context, our results demonstrate that older drivers drive less efficiently, presenting a higher SDLP and driving longer distances outside their lane, even though they try to correct the vehicle’s position, as evidenced by the higher SD of the steering wheel angular velocity. These results are in general agreement with previous studies, which found that older drivers have a greater incidence of lane excursions [ 34 ], more difficulties changing lane [ 35 ], and less control over the vehicle’s position in unexpected events or divided attention tasks [ 27 ]. The reduced visual capacity observed in older drivers could be responsible for most of these changes, as it affects visual guidance abilities and visual attention span, making older drivers slower and less accurate when detecting all the stimuli on the road [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…All participants drove in a scenario with identical traffic flow and the same number of peripheral events as above. More information on this simulated environment can be found elsewhere [ 27 , 28 ]. Participants received at least two training sessions separated by a seven-day washout period.…”
Section: Methodsmentioning
confidence: 99%
“…The study by van Rijn et al [10] evaluated the properties of several glare devices, concluding that the measurement of intraocular straylight correlates well with the detrimental effects of glare on perception, being particularly important in subjects with cataracts. Importantly, the work of Ortiz et al [21] showed a significant correlation between straylight and driving performance, for example in the distance travelled invading the opposite lane, SDLP, and the number of collisions. Moreover, other authors have proposed a cut-off limit for straylight, beyond which driving risk increases.…”
Section: Discussionmentioning
confidence: 99%
“…The second section was a winding mountain road of onelane single carriageway 6 km long, with variable speed limit of 40 km/h to 90 km/h, no buildings, and moderate traffic. More information on the characteristics of the sections can be found elsewhere [21]. All participants underwent three training sessions with a washout period of 7 days between them.…”
Section: Driving Simulator Experimental Designmentioning
confidence: 99%
“…Distraction reduce the driver's perception and decision making capability by diverting his/her attention from the primary task of driving to secondary activities [2]. In-vehicle entertainment systems (audio/video players) and gadgets (GPS and mobile communication) are among the leading causal factors of driver distraction [3,4]. Moreover, a driver may be distracted because of engagement in eating/drinking, smoking or talking to the passengers during driving [5,6].…”
Section: Introductionmentioning
confidence: 99%